White light emission from novel host-sensitized single-phase Y2WO6: Ln3+ (Ln3+=Eu3+, Dy3+) phosphors. Issue 12 (September 2016) - Xiong, F.B.; Han, C.Y.; Lin, H.F.; Wang, Y.P.; Lin, H.Y.; Shen, H.X.; Zhu, W.Z.
Abstract: A series of Eu 3+ - or Dy 3+ -doped and Eu 3+ /Dy 3+ co-doped Y2 WO6 in pure phase was synthesized via high-temperature solid-state reaction. X-ray diffraction, diffuse reflection spectra, photoluminescence excitation and emission spectra, the CIE chromaticity coordinates and temperature-dependent emission spectra were exploited to investigate the phosphors. Upon UV excitation at 310 nm, efficient energy transfer from the host Y2 WO6 to dopant ions in Eu 3+ or Dy 3+ single-doped samples was demonstrated and those phosphors were suitable for the UV LED excitation. The intense red emission was observed in Y2 WO6 : Eu 3+, and blue and yellow ones were observed in Y2 WO6 : Dy 3+ . Concentration quenching in Y2 WO6 : Dy 3+ phosphors could be attributed to the electric dipole-dipole interaction. In Eu 3+ /Dy 3+ co-doped Y2 WO6 phosphors energy transfer process only took place from the host to Eu 3+ /Dy 3+ ions and warm white-light emission can be obtained by adjusting the dopant concentrations. The temperature-dependent luminescence indicated Eu 3+ /Dy 3+ co-doped Y2 WO6 was thermally stable. Our overall results suggested that Y2 WO6 : Ln 3+ (Ln 3+ =Eu 3+, Dy 3+ ) as warm white-light emitting host-sensitized phosphor might be potentially applied in WLEDs.